2021
DOI: 10.1038/s41598-021-85983-z
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory image of the stability of people with multiple sclerosis and atrial vertigo based on posturography examination

Abstract: Pathophysiology of balance disorders due to multiple sclerosis (MS) and atrial vertigo (AV) is different. We evaluated posture stability when maintaining balance in people with MS presenting symptoms of ataxia and those with AV. We included 45 women (15 with MS; 15 with AV; 15 controls). A posturography platform was used to measure balance parameters. To characterize the image of stability and the compensation of balance disorders, the surface area of the stabilogram (SAS), vision control index (VCI) and the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Analysis of COP movements provides a wealth of information about postural stability. Based on the recorded data, it is possible to assess the variability of body deflection when maintaining balance in a standing position and this assessment is particularly important in conditions of disturbed postural stability [29].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of COP movements provides a wealth of information about postural stability. Based on the recorded data, it is possible to assess the variability of body deflection when maintaining balance in a standing position and this assessment is particularly important in conditions of disturbed postural stability [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that balance requires vestibular, visual and somatosensory inputs (both proprioceptive and exteroceptive information) [ 5 ]. Therefore, vestibular deficits (vertigo or dizziness, for example) [ 6 ], visual impairments (such as, diplopia) [ 7 ], and proprioceptive disorders due to fatigue and muscle weakness [ 8 ] may impair balance in PwMS [ 9 ]. All these issues affect postural control and different balance domains (functional, static or dynamic), reducing patients’ confidence in their balance and increasing the risk and fear of falling [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…All pathological or functional changes that impair the functioning of the postural control system or the executive system are reflected in disturbances of posture balance and stability [ 47 , 48 ]. Dysfunctions of the sense organs and deep sensation disturb measurements of body balance [ 49 ]. In our own research, the exclusion criteria involved vision defects and problems with maintaining a balance of the body correlated with the aforementioned diseases, which allowed us to minimize the factors disturbing the reading of the balance parameters analyzed on the Zebris PDM-L platform.…”
Section: Discussionmentioning
confidence: 99%